Land Use Planning for Urban Flood Risk Management - World Bank (World Bank, Washington, DC, 2017)
This note offers policy makers and practitioners an overview of the key aspects of land use planning used to manage flood risks in cities across the world. It includes examples from developed and developing countries to provide insight into what has worked in different contexts.